2002
DOI: 10.2139/ssrn.321043
|View full text |Cite
|
Sign up to set email alerts
|

Geo-Additive Models of Childhood Undernutrition in Three Sub-Saharan African Countries

Abstract: We investigate the geographical and socioeconomic determinants of childhood undernutrition in Malawi, Tanzania and Zambia, three neighbouring countries in Southern Africa using the 1992 Demographic and Health Surveys. In particular, we estimate models of undernutrition jointly for the three countries to explore regional patterns of undernutrition that transcend boundaries, while allowing for country-specific interactions. We use geo-additive regression models to flexibly model the effects of selected socioecon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
39
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 17 publications
8
39
0
Order By: Relevance
“…Studies elsewhere as well as in the country supported the non random distribution of child malnutrition. Studies from West Africa [23], SSA [24], Nigeria [25] and Ethiopia [16, 26] indicated a clear spatial pattern in child under- nutrition across different geographical locations [16, 25–27]. …”
Section: Discussionmentioning
confidence: 99%
“…Studies elsewhere as well as in the country supported the non random distribution of child malnutrition. Studies from West Africa [23], SSA [24], Nigeria [25] and Ethiopia [16, 26] indicated a clear spatial pattern in child under- nutrition across different geographical locations [16, 25–27]. …”
Section: Discussionmentioning
confidence: 99%
“…DHS and MICS include a wide variety of other variables that can be used to assess the factors driving undernutrition. In fact, a vast literature has emerged as a result of the wide availability of these data sets (e.g., Smith et al 2003;Foraita et al, 2008;Kandala et al, 2009). Correspondingly, these surveys can be used to design and monitor nutrition interventions.…”
Section: Strengths and Weaknesses Of Anthropometric Approachesmentioning
confidence: 99%
“…Even during the dry season, due to the increase in evaporation rate and decrease in groundwater level, cultivation of winter crops and aquaculture is prohibited. Villagers remain isolated with poor road accessibility and transport links, which may have implications for access to health facilities and other welfare services (Kandala et al, 2009). These issues deserve closer attention: this study is merely able to highlight the important spatial patterns of undernutrition without being able to fully explain them.…”
mentioning
confidence: 95%